The Study of Feminism in The Novel Natalia Nem, Perem puan Muyu Who Is Silent by Marthen Luter Wambarop - Tobias Nggaruaka,; Lay Riwu,; Nova Lina Sari Habeahan, (Technium Social Sciences Journal, 2023)
Natalia Nem, with the facial expressions of a charming woman with natural characteristics and style, sometimes becomes a topic of conversation among the public, not because of her beauty, but because of the problem she faces, namely getting pregnant out of wedlock. This research aims to explore the female face in the novel Natalia Nem by Marthen Luther Wambarop. The book raises an actual event with a cultural background of life in South Papua. This research method uses a qualitative approach with a critical type of feminism. The results of this study indicate that Natalia Nem describes situations in (1) misfortune, (2) losing hope, (3) falling into a false hope, and (4) giving up on God.